New rare earth hafnium oxynitride perovskites with photocatalytic activity in water oxidation and reduction. Issue 12 (25th January 2018) - Black, Ashley P.; Suzuki, Hajime; Higashi, Masanobu; Frontera, Carlos; Ritter, Clemens; De, Chandan; Sundaresan, A.; Abe, Ryu; Fuertes, Amparo
Abstract : RHfO2 N perovskites with R = La, Nd, and Sm represent the first examples of quaternary hafnium oxynitrides and are active as photocatalysts in the overall water splitting reaction. Abstract : RHfO2 N perovskites with R = La, Nd and Sm show a GdFeO3 -type structure and are semiconductors with band gaps of 3.35, 3.40 and 2.85 eV and relative dielectric constants of 30, 16 and 28 respectively. These compounds have adequate reduction and oxidation potentials to conduct the overall water splitting reaction, and the analogous perovskite LaZrO2 N with a band gap of 2.8 eV shows photocatalytic activity under visible light irradiation for O2 evolution.